How Much Autonomy Do International Branch Campuses Really Have? - Clifford, Megan; Kinser, Kevin (International Higher Education, 2016)
The governments of several developing nations have used public funds to support International Branch Campuses (IBCs). These countries often have specific requirements and regulations that the IBCs must meet. As a result, some of the IBC’s most fundamental financial, academic and governance decisions are determined or heavily influenced by the host nation. These practices compromise the financial autonomy and academic autonomy of IBCs and threaten their sustainability and quality.